The Concept of the Arab-Islamic Mind and the Modernization of Islamic Thought - Yesdaulet Yergeldi; Kudaiberdi Bagasharov; Murat Smagulov (Journal of Islamic Thought and Civilization, 2026)
This article provides a comprehensive analysis of the pressing challenges confronting the Islamic world, particularly focusing on the interrelated issues of ignorance, poverty, and disunity. It argues that ignorance perpetuates poverty, which in turn fuels extremism, creating a cycle that hinders social and economic progress. The article underscores the critical role of education and intellectual reform in breaking this cycle, emphasizing that a lack of access to quality education prevents individuals from contributing meaningfully to societal development. It also highlights the spiritual dimensions of these challenges, suggesting that they reflect a departure from divine principles as outlined in Islamic teachings.The article delves into the historical and intellectual roots of the "Arab-Islamic mind," a concept that has been extensively critiqued by prominent scholars such as Mohammad Arkoun and Mohammad Abid al-Jabri. These thinkers advocate for a transformative approach to Islamic thought, urging the integration of modern scientific methodologies and a broader, more inclusive interpretation of Islamic teachings to address contemporary challenges. The discussion is framed within the context of colonialism, which disrupted traditional intellectual and cultural frameworks, and the failure of the Nahda (Renaissance) movement, which aimed to modernize Islamic societies but fell short of its goals.A significant portion of the article is devoted to the linguistic and epistemological crises that have hindered intellectual progress in the Islamic world. The decline of classical Arabic and the proliferation of foreign languages in education have created a disconnect from Islamic heritage (turāth), exacerbating the intellectual stagnation. The article concludes by advocating for the development of a unified system that harmonizes Islamic principles with modern knowledge, emphasizing the need for a collective effort to overcome socio-economic and intellectual challenges. It calls for a renewed focus on education, language, and critical engagement with Islamic tradition as essential steps toward revitalizing the Islamic world and fostering unity and progress.